COVID-19 Patient Mortality with Convalescent Plasma Therapy: Meta-Analysis - Fathiyyatu Assa’diy Firda; Bhisma Murti; Cri Sajjana Prajna Wekadigunawan (Journal of Epidemiology and Public Health, 2021)
Background: The use of convalescent plasma was recommended as empiric treatment during the Ebolavirus outbreak in 2014, and a protocol for the treatment of Middle East Respiratory Syndrome coronavirus (MERS) with convalescent plasma was created in 2015. These findings raise the hypothesis that the use of convalescent plasma transfusion may be beneficial in SARS-infected patients. -CoV-2. The aim of this study was to estimate the mortality risk of COVID-19 patients with convalescent plasma therapy.Subjects and method: A systematic review and meta-analysis was carried out by collecting articles from the Google Scholar, PubMed, and Science Direct databases. The articles were screened using the PICO model, including: (1) Population= confirmed COVID-19 patients, (2) Intervention= conva